Closed loop control of DC-DC converters using PID and FOPID controllers - Aseem K; Selva Kumar S (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Fractional order controllers are nowadays used in various power electronic converters as it is giving superior control performance compared with conventional PID controllers. This paper presents the closed loop control of different DC-DC converters using PID controllers and Fractional Order PID (FOPID) controllers. The closed loop control of the basic converters such as buck, boost, buck-boost converters and dual input single output DC-DC converters were designed, modeled and analyzed using conventional PID controller and FOPID controllers. The performance of the controllers are compared in terms of the different time domain specifications like overshoot, rise time, settling time, etc. and simulated in MATLAB Simulink platform. For all types of the DC-DC converters, FOPID controller gives far better performance compared with conventional PID controllers.